Developing French Teaching Materials in Senior High School by Integrating Portofolio Europeen des Langues (PEL) - Ekowati, Sri Harini; Purbarini, Asti (International Journal of Active Learning, 2016)
Senior High School (SMA) is a school that provides French language lessons to students majoring in natural sciences and social sciences. There are also high schools that open special French class for students and some schools put French as a lesson for extra-curricular activities. From the analysis of the textbooks used by high school teachers, it is concluded that the textbooks / instructional materials that they use are less up to date and some are using compilation (compilation of texts drawn from various sources). Language teaching materials in the European Union are already equipped with Portfolio Europen des Langues (PEL) and of the literature found, PEL provides many benefits to learning foreign language. The benefit of PEL is not only for teachers but also for students. The above mentioned have been the reason to conduct this study, developing French teaching materials in high schools that integrate Portfolio Europen des langues (PEL) for French language learners in Indonesia. To initiate this study, the analysis of textbooks used by several high schools in Jakarta and surrounding areas had been conducted. Furthermore, it is then continued with the analysis of the needs of the PEL. To obtain the necessary data, this study uses interview questionnaire.The next step is to arrange French language teaching materials prototype for high school that integrates PEL. The prototype is reviewed by two experts in their field and have been revised, and then limited trials for high schools are conducted.How to CiteEkowati, S. H., & Purbarini, A. (2016). Developing French Teaching Materials in Senior High School by Integrating Portofolio Europeen des Langues (PEL). International Journal of Active Learning, 1(1).